2021
DOI: 10.21203/rs.3.rs-244844/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Effect of Live Demonstration and Flipped Classroom with Continuous Formative Assessment on Dental Students’ Orthodontic Wire-bending Performance

Abstract: Background: In some dental schools, undergraduate students are taught wire-bending to train their manual dexterity. Traditionally, live demonstration (LD) was used as the sole teaching method until recently, either live video demonstration or flipped classroom (FC) teaching are being employed. Continuous formative assessment can be used as a systematic approach for personalised learning. This allows monitoring of the students’ progress and enhances learning by enabling students to identify their strengths and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…Majority of the students (80%) always or frequently watched the entire length of the video demonstrations, and 75% of students watch the video demonstrations more than once. 17 However, the qualitative findings of this study are in agreement with the reported literature, in which FC is received positively by students as an effective tool for teaching preclinical skills, and in this context, orthodontic component wire-bending skills.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Majority of the students (80%) always or frequently watched the entire length of the video demonstrations, and 75% of students watch the video demonstrations more than once. 17 However, the qualitative findings of this study are in agreement with the reported literature, in which FC is received positively by students as an effective tool for teaching preclinical skills, and in this context, orthodontic component wire-bending skills.…”
Section: Discussionsupporting
confidence: 90%
“…4,15,17,23 The mean wire-bending score for FC for this current study was significantly higher than LD for two of the six assignments, namely the Adams clasp and Z-spring. 17 However, qualitative research on FC approaches is scant and is regarded as "under-evaluated, under-theorized, and under-researched in general" by Abeysekera and Dawson. 28 O'Flaherty and Phillips also commented that "constructs such as engagement are not always easily reduced to measurable items on survey instruments or a reflection of examination performance and so warrant further investigation."…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…Surgery, Obstetrics-Gynaecology, ENT, Dermatology etc and shows promising results for Competency Based Education (CBE). [20][21][22][23] However, to promote DOPS in dentistry, more research will further support the cause. "Lest not forget" dental academics during present times must be evidence based, made student, patient and community centered; in line with modern principles of dental-medical education.…”
Section: Directly Observed Procedural Skills (Dops) and Clinical Dental Academicsmentioning
confidence: 99%
“…In dentistry, the inverted classroom model has been implemented in several disciplines such as prosthodontics [Nishigawa et al, 2017], dental anatomy [Kellesarian, 2018], oral and maxillofacial surgery [Bock et al, 2020], orthodontics [Sivarajan et al, 2021], periodontology [Crome et al, 2021], dental materials and biomaterials [Binnie and Bonsor, 2021], and pediatric dentistry [Gallardo et al, 2021]. Recently, a systematic review concluded that an inverted classroom, implemented in undergraduate dental education, improves student satisfaction in most of the studies, while its effect on academic performance, particularly for skill development, needs more research [Vanka et al, 2020].…”
Section: Introductionmentioning
confidence: 99%